Antioxidant activity and compound constituents of gamma-irradiated black rice (Oryza sativa L.) var. Cempo Ireng indigenous of Indonesia - Venty Suryanti; Riyatun; SUHARYANA SUHARYANA; Sutarno; Ozi Adi Saputra (Society for Indonesian Biodiversity, 2020)
Abstract. Suryanti V, Riyatun, Suharyana, Sutarno, Saputra OA. 2020. Antioxidant activity and compound constituents of gamma-irradiated black rice (Oryza sativa L.) var. Cempo Ireng Indigenous of Indonesia. Biodiversitas 21: 4205-4212. Nowadays, black rice is gaining consumer interest because of its health benefit. Due to the high content of antioxidant compounds such as phenolics and flavonoids, the nutritional profile of black rice is much better than any other rice varieties. Anthocyanins, pigment with powerful antioxidant properties, give a vibrant color to the rice. The antioxidant activity and chemical constituents of the non-irradiated and gamma-irradiated black rice Oryza sativa L. var Cempo Ireng were investigated. The total phenolic content was determined based on the reaction of the Folin-Ciocalteu reagent with samples. Total anthocyanin was determined by the pH differential method. Antioxidant activity was fulfilled using DPPH method. The results revealed that non-irradiated and gamma-irradiated black rice were categorized as potent antioxidants. It is noted that irradiation increased antioxidant activity and changed the chemical components of black rice. Both of non-irradiated and irradiated black rice contains simple phenolics and flavonoids, including anthocyanins. Non-irradiated and irradiated black rice possess similar types of secondary metabolites, with different chemical content. The non-irradiated black rice contains anthocyanins of cyanidin-3-O-glucoside, whereas the irradiated black rice possesses anthocyanin of peonidin-3-O-glucoside. Additionally, irradiated black rice contains terpenoids, which increased its antioxidant activity compared to the control.